PENGARUH PENDEKATAN PROBLEM BASED LEARNING (PBL) BERBANTUAN AUGMENTED REALITY (AR) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DI SMK NEGERI 1 LEBONG - Sri Mulianti; Agus Susanta; Hanifah Hanifah; Saleh Haji (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to determine the effect of the Problem Based Learning Approach assisted by Augmented Reality on the Ability to Solve Mathematical Problems at SMK Negeri 1 Lebong. This type of research was a Quasi Experiment which was carried out at Lebong 1 State Vocational School in class X for the 2022/2023 Academic Year with the research population being all of class X, totaling 88 people. Samples were taken by random sampling technique for class X Multimedia 1, totaling 22 people as the experimental class and X Multimedia 2, totaling 20 people as the control class. Data collection instruments were carried out through tests with data analysis techniques using MANOVA. The results showed that there were: (1) The effect of the Problem Based Learning approach with the help of Augmented Reality on the ability to solve mathematical problems. (1) The effect of the Augmented Reality Problem Based Learning approach on problem solving ability is 58.6%. (2) The achievement of mathematical problem-solving skills of class X Multimedia 1 students taught by AR-assisted PBL approach is higher than the class taught by conventional learning models